Influence of different Temperatures and Substrates on the Germination of Munguba (Pseudobombax munguba (Mart. & Zucc.) Dugand.) - P. Barbosa, Antenor; Oliveira, Michele Braule P. R. de; Pereira, Adrielly O. (International Journal of Environment, Agriculture and Biotechnology, 2022)
Due to the ecological and economic importance of the species Pseudobombax munguba (Mart. & Zucc.) Dugand. (Munguba), it is necessary to investigate the most appropriate conditions for conducting its germination process. Therefore, the objective of this work was to evaluate seed moisture, number of seeds/kg, and the influence of different temperatures and substrates on the process of seed germination. The initial seed moisture was evaluated with samples containing four replicates of 10, 20, 30, 50, 60, 70, 80, 90 and 100 seeds dried in an oven at 105±3ºC. Germination was tested in three different substrates: sand, vermiculite, and Germitest® paper rolls (three sheets/roll) at constant temperatures of 25, 30 and 35ºC in a germination chamber. The number of 50 seeds per replicate had more homogeneous representation with 7.2% moisture. Sand or vermiculite substrates at a temperature of 25°C can be indicated to conduct the germination of the species under controlled conditions. Germination rates in sand substrate reached 69% when assessed for root protrusion, and 53% for seedling formation. Germination rates in vermiculite were 74% for root protrusion and 56% for seedling formation. The initial development was homogeneous and there were higher rates of germination speed in both substrates when assessing seedling formation.